Gambling in Contests - Christian Seel; Philipp Strack (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2012)
This paper presents a strategic model of risk-taking behavior in contests. Formally, we analyze an n-player winner-take-all contest in which each player decides when to stop a privately observed Brownian Motion with drift. A player whose process reaches zero has to stop. The player with the highest stopping point wins. Contrary to the explicit cost for a higher stopping time in a war of attrition, here, higher stopping times are riskier, because players can go bankrupt. We derive a closed-form solution of the unique Nash equilibrium outcome of the game. In equilibrium, the trade-off between risk and reward causes a non-monotonicity: highest expected losses occur if the process decreases only slightly in expectation.
urn:nbn:de:bvb:19-epub-13179-7
Keywords: C72; C73; D81; 330; Discontinuous games; Contests; Relative performance pay; Risktaking behavior; Entscheidung bei Risiko; Glücksspiel; Nichtkooperatives Spiel; Test